2006
DOI: 10.1097/01.sap.0000229002.09605.5d
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinoma of Scalp in Patients With History of Childhood Therapeutic Radiation

Abstract: BCC in irradiated scalp has a more aggressive behavior and may need a more aggressive surgical resection. Also, these patients should be under close observation because there is a higher chance for tumor recurrence and also new lesions occurring elsewhere in the scalp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Previous studies showed that BCC in irradiated scalp has a more aggressive behaviour and a higher chance for tumour recurrence. 34 However, further research is recommended.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that BCC in irradiated scalp has a more aggressive behaviour and a higher chance for tumour recurrence. 34 However, further research is recommended.…”
Section: Discussionmentioning
confidence: 97%
“…BCC in irradiated scalp was reported to have a more aggressive behavior that necessitates a wider surgical resection [70]. Hassanpour et al reported that these patients also demonstrated higher rates of tumor recurrence and second primary tumors occurring elsewhere in the scalp, so it has been suggested that these patients should be regularly followed up [70] ( Table 2).…”
Section: Profession Urban and Rural Populationsmentioning
confidence: 98%
“…Similar to reporting for atomic bomb survivors and hematopoietic cell transplantation, there is an inverse relationship between BCC risk and age at radiation exposure (16, 42, 43). Although BCC is generally characterized by slow growth, minimal soft tissue invasiveness and high cure rates, other studies showed that BCC developed in irradiated scalp skin tended to be more aggressive and more prone to recurrence (44, 46). Studies depicting the molecular mechanism underlying pathogenesis of aggressive radiation-induced BCCs are few.…”
Section: Introductionmentioning
confidence: 99%